Overcoming Resource Nexus Conflicts With a Normative-Institutional Approach: A Case Study of Brazil - Carvalho, Priscila; Spataru, Catalina (Frontiers in Water, 2023)
Water-energy nexus research highlights the need for co-management across water and energy sectors, whereby joint planning and solutions under better integrated governance of resources could make action more efficient and cost-effective to advance the SDGs. A gap remains in the literature with regards to the normative dimension of the resource nexus. At the background or resource nexus conflicts there are norms, which need to be considered and applied in the resolution of disputes. Brazil has been chosen as case study because of rising conflicts around its high dependency on water and hydropower generation to keep affordable tariffs, while securing multiple water uses. Hydrological factors (e.g., prolonged droughts) and non-hydrological factors (e.g., chronic delays in delivery of new plants and transmission lines) have impacted on water availability, which led to constraints for hydropower generation, with cascading economic, social and environmental impacts. Electricity prices have risen, while water quantity and quality have decreased, affecting multiple users and ecological integrity of rivers. All of which impact negatively on livelihoods and water services and sanitation, aggravated by the fact that electricity represents one of the fastest growing costs for Water services, Sanitation and Hygiene (WASH) suppliers. The novel combination of research methods based on metrics, historical-institutional analysis, questionnaire, and in-depth interviews served as instruments for the assessment of the water-electricity nexus issues and development of a new legal approach to manage conflicts arising in Brazil. Most of the existing work has favored integration of water and electricity sectors based on quantitative approach to address the interlinkages between them and tackle trade-offs. However, from a legal perspective, very little is known about how these sectors could be better integrated in practice. This study proposes a normative-institutional approach that offers a flexible, integrated, and adequate legal treatment to overcome the conflicts between water and electricity in the context of their asymmetrical governance, policies, regulation, planning and environmental injustices. Split in substantive, institutional, and procedural dimensions this approach is necessary to enhance participatory and equitable resource governance based on the laws of balancing legal principles, rational, inclusive, and transparent procedures. It was concluded that for water-electricity nexus thinking to be connected to the idea of integration it will be necessary to consider justice by taking a normative-institutional approach that can support advances to the SDGs in more holistic and fair ways.